A qualitative exploration of counterfeit, substandard, spurious, and adulterated drugs in Pakistan: A perspective of drug law experts - Farooq Bashir Butt; Hamid Saeed; Zobia Mubarak; Syed Atif Raza; Usman Rashid Malik; Furqan Khurshid Hashmi (PLoS ONE, 2025)
Objectives The issue of quality of medicine is a worldwide phenomenon and counterfeit, substandard, spurious, and adulterated (CSSA) drugs are a substantial threat to public health. This issue is rampant in the context of low-middle-income countries such as Pakistan. The current study involved a phenomenology-based qualitative approach to explore these drugs’ perception, knowledge, practice, and issues in combating this menace. Methods A semi-structured interview guide was developed. Eleven drug law experts were interviewed through a purposive sampling technique. All interviews were audio recorded, transcribed verbatim, and analysed using a framework analysis approach, yielding seven distinct themes. Results The results showed that CSSA drugs are a serious public health threat and drug law experts confirmed its prevalence in the market. They indicated shortcomings in legislation up to the extent of undue amendments, failure to interpret and implement the law by regulators, ineffective law enforcement machinery, the sub-optimum performance of quality control boards, drug testing laboratories, and courts, and the dubious role of rogue middlemen and wholesalers in drug supply chain and corruption were salient issues highlighted. Conclusion The study revealed that proper drug surveillance, ensuring the presence of a pharmacist, enforcing the law, securing the supply chain, infrastructure for a drug control regime, and training regulators can help tackle this problem.